Species limits, phylogeographic and hybridization patterns in Neotropical leaf frogs (Phyllomedusinae) - Brunes, Tuliana O.; Alexandrino, Joao; Baeta, Delio [UNESP]; Zina, Juliana; Haddad, Celio F. B. [UNESP]; Sequeira, Fernando (Wiley-Blackwell, 2014)
The taxonomy of many species is still based solely on phenotypic traits, which is often a pitfall for the understanding of evolutionary processes and historical biogeographic patterns, especially between closely related species due to either phenotypic conservatism or plasticity. Two widely distributed Neotropical leaf frogs from the Phyllomedusa burmeisteri species group (P.burmeisteri and Phyllomedusa bahiana) constitute a paramount example of closely related species with relatively unstable taxonomic history due to a large phenotypic variation. Herein, we analysed similar to 260 individuals from 57 localities distributed across the range of the two species to contrast individual phenotypic with an integrative phylogenetic and phylogeographic multilocus approach. We aim to clarify species limits, investigate potential undocumented diversity and examine to what extent taxonomic uncertainties could lead to misleading hypotheses on phylogeographic and interspecific hybridization patterns. Our molecular analysis supports the recognition of the two currently defined species, providing evidences for one novel and highly divergent evolutionary unit within the range of P.burmeisteri, which encompasses its type locality (Rio de Janeiro city). Spatial patterns of genetic and the colour of the hidden areas of the thigh was not congruent, varying considerably both within and between populations of both species. Genetic data showed signs of admixture between both species but do not corroborate the previously inferred wide area of introgression based on the distribution of the intermediate phenotype. Our results suggest that phenotypic variation can result from local adaptations, geographic isolation and/or evolutionary processes and, thus, cannot be used to reliably diagnose P.burmeisteri and P.bahiana. Globally, this study underscores the need of a geographical broad sampling of widespread species and the combination of molecular and phenotypic data to delineate species limits and phylogeographic patterns in species with complex taxonomy.